1997
DOI: 10.1037/0022-0663.89.4.652
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of handwriting problems in beginning writers: Transfer from handwriting to composition.

Abstract: Almost 700 children were screened to identify 144 1st graders at risk for handwriting problems who were randomly assigned to 1 of 6 treatment conditions. Treatment was delivered to groups of 3 that met twice a week in 20-min sessions until they completed 24 lessons. Five groups received 10 min of different kinds of handwriting instruction. The contact control group received 10 min of phonological awareness training. All 6 groups composed and shared their writing for 10 min. Converging evidence across multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
300
2
20

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(341 citation statements)
references
References 27 publications
19
300
2
20
Order By: Relevance
“…A way of teaching handwriting is to explain the form and the order of letter strokes in additional to copying exercises [14,15,16]. Children must be able to both perceive the shape of the model and evaluate the deviation between their own handwriting product and the standard.…”
Section: Introductionmentioning
confidence: 99%
“…A way of teaching handwriting is to explain the form and the order of letter strokes in additional to copying exercises [14,15,16]. Children must be able to both perceive the shape of the model and evaluate the deviation between their own handwriting product and the standard.…”
Section: Introductionmentioning
confidence: 99%
“…A research programme to consider what intervention might be most effective, and taking into account work already carried out in other countries (e.g. Berninger et al, 1997;Christensen, 2005;Graham & Harris, 2005;Graham, Harris & Fink, 2000;Jones & Christensen, 1999) using a relatively simple alphabet writing task designed by Berninger et al (1991), could then be undertaken. This programme of research has the potential to benefit young writers, particularly boys, who struggle to compose throughout their primary and secondary schooling.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Berninger et al (1997), Grade 1 (age 7) children identified as at risk for handwriting difficulties were assigned to one of six intervention groups: five handwriting treatment groups or a phonological awareness treatment condition. Performance on a standardised writing test (of composition, not just handwriting) improved for children assigned to the handwriting groups, but especially for the most successful handwriting group.…”
Section: Pedagogic Ways Forwardmentioning
confidence: 99%
“…Ces études montrent aussi comment il adapte sa motricité fine à l'acte graphique (Zesiger, 1995). Des auteurs comme Graham, Harris et Finck (2000), ou encore Berninger et al (1997) ont apporté un éclairage sur les relations chez les enfants en première année d'école primaire, entre performances en écriture manuscrite de lettres individuelles et écri-ture de lettres de mémoire, de copies de paragraphes.…”
Section: Lecture éCriture Et Copie D'écritunclassified